Kajian terhadap Artikel Ilmiah tentang Fungsi dan Bentuk Register Bahasa dalam Berbagai Ruang Sosial - Ilawati Ilawati; Kuntoro Kuntoro (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study investigates the forms and functions of language registers across diverse social contexts, including traditional markets, professional communities, digital media, and podcasts, through a literature review of ten scholarly articles published in accredited journals between 2021 and 2025. Employing a descriptive qualitative approach, the data were analyzed to identify linguistic variations that reflect specific social contexts, situations, and communicative purposes, aligned with Halliday’s (1978) concept of register, which emphasizes language adaptation to social contexts. The findings indicate that register forms encompass specific words, phrases, abbreviations, acronyms, and reduplications. Their communicative functions include instrumental, interactional, representational, and regulative roles, which enhance communication efficiency and preserve cultural identity. This study provides insights for researchers, educators, and practitioners to leverage registers in contextual communication.